Sexual Crime and Circles of Support and Accountability (Sexual Crime, 2018)
This book offers a collection of original contributions to current research available on Circles of Support and Accountability (CoSA) by engaging with current literature and unpublished research in the field. The book explores the role of narrative identity in desistance from sexual crime and how CoSA maps onto this, as well as a history of CoSA across the world. The text then moves into an empirical section, reporting on some unpublished findings, including an evaluation of a new prison-based CoSA in the UK. Lastly, the experiences of service users and the influence of media perceptions are explored, offering a space for the 'unheard voices' as well as consideration of future directions for practitioners. The book is relevant not just to psychologists, criminologists, social workers and students, but to practitioners and the general public with an interest in learning about CoSA. The editors of this volume have all been involved in the setting up of the Safer Living Foundation, a charity formed in 2014 to reduce and prevent sexual offending. .